2008
DOI: 10.1590/s0004-28032008000400004
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação do escore MELD em pacientes submetidos a transplante de fígado: análise retrospectiva da sobrevida e dos fatores preditivos a curto e longo prazo

Abstract: RESUMO -Racional -Utiliza-se o escore MELD (Model End-Stage Liver Disease) para o prognóstico da mortalidade em lista de espera para transplante de fígado e, em alguns estudos, para predição da sobrevida pós-operatória a longo prazo. Objetivo -Verificar a aplicação do escore MELD como predição da sobrevida após o transplante. Métodos -Por intermédio de dados coletados prospectivamente efetuou-se um estudo de coorte longitudinal retrospectivo em 232 pacientes. Excluíram-se os retransplantes, insuficiência hepát… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
2
13
0
1
Order By: Relevance
“…Normally, AUC values e" 0.7 are considered clinically useful, whereas values d" 0.5 are related to scores with no discriminatory power 3,16,17 . Based on the results found, the preoperative MELD score showed low overall accuracy for predicting survival after HT, similar to that described in other Brazilian studies 3,18 . Also, since the survival of transplanted patients with HCC is influenced by parameters related to the tumor 19 , we performed analyzes stratified between subgroups HCC and non-HCC.…”
Section: Methods Methods Methods Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…Normally, AUC values e" 0.7 are considered clinically useful, whereas values d" 0.5 are related to scores with no discriminatory power 3,16,17 . Based on the results found, the preoperative MELD score showed low overall accuracy for predicting survival after HT, similar to that described in other Brazilian studies 3,18 . Also, since the survival of transplanted patients with HCC is influenced by parameters related to the tumor 19 , we performed analyzes stratified between subgroups HCC and non-HCC.…”
Section: Methods Methods Methods Methodssupporting
confidence: 87%
“…This low proportion of patients with high scores likely contributed to minimize its overall accuracy for predicting survival after TH in this series. Intraoperative transfusion of red blood cells has often been related to lower survival after liver transplants 18,[25][26][27][28] , which can also be seen in this series, which identified a strong influence of the transfusion of blood components in the medium-term survival of transplant patients. This negative effect of blood transfusions probably stems from immunomodulation related to transfusions and changes of its components from storage process 29 , which may increase the risk of nosocomial infections, acute lung injury and development of autoimmune diseases in the long term 30 .…”
Section: Methods Methods Methods Methodssupporting
confidence: 66%
“…Most of the studies (21,22,24,25,27,28,30,32) assessed the relationship between exercise capacity and the Child-Pugh scoring -this model was created to predict life mortality and expectancy in patients with hepatic cirrhosis (38,39). Even though some studies did not find a negative correlation between exercise capacity and Child-Pugh scoring (21,22,34,35), it has been suggested that hepatic cirrhosis can affect cardiorespiratory capacity during exercise (24,25,27,28,30,32).…”
Section: Methodsmentioning
confidence: 99%
“…1 A study published in the United States in 2014 indicates that as of July 26 2013, there were 118,895 Americans waiting for organ transplants, among which 15,773 were waiting for liver transplants. 2 World-wide experiments confirm the success of liver transplantation as a definitive cure for hepatocellular carcinoma, the seventh most common type of cancer worldwide since it allows the total removal of the tumor, [3][4] and is also indicated for patients with decompensated cirrhosis and acute liver failure.…”
Section: Introductionmentioning
confidence: 99%
“…9 Liver transplants have been performed in Brazil since 1968. 1 As a result of the technological advances and improvements in surgical techniques, it was possible to optimize the time of surgery and recovery of patients undergoing liver transplantation. Twenty years ago, the surgery lasted between 17 and 24 hours and currently on average, it takes five hours.…”
Section: Introductionmentioning
confidence: 99%